REKONSTRUKSI KONSEP KEPEMILIKAN (AL-MILKIYAH) DALAM EKONOMI SYARIAH MODERN - Siti Kholijah (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
The concept of ownership (al-milkiyah) plays a pivotal role in Islamic economic systems as an instrument of justice and social welfare. However, the rise of digitalization and the emergence of intangible assets such as personal data, digital rights, and blockchain-based assets demand a reconstruction of ownership to remain relevant in contemporary contexts. This study aims to analyze and reconstruct the concept of al-milkiyah within modern Islamic economic thought through an in-depth literature review of classical and contemporary sources. Using a qualitative method and thematic synthesis integrated with the framework of maqashid al-shariah, the study finds that ownership is not an absolute right but a trust carrying social responsibility, grounded in justice and collective benefit. The reconstruction includes the recognition of digital and intangible assets, provided they meet principles of legal certainty, utility, and protection against speculation or excessive uncertainty. The integrative-interconnective approach enables adaptive interpretation of ownership concepts while preserving core Islamic values. The novelty of this study lies in synthesizing classical and contemporary thought with an integrative approach to propose a contextual framework of al-milkiyah. These findings are expected to contribute to developing Islamic economic theory, policymaking, and the creation of halal digital products.